Furo Wariboko’s Interactional Emphasis in A. Igoni Barret’s Blackass - Al Farisi, Mohammad Salman (English Literature Study Program, 2023)
The concept of identity theory highlights that individuals may possess multiple identities, elucidated through prominence hierarchy and salience hierarchy. This thesis aimed to explore the prominence hierarchy and its effects on Furo Wariboko, the central character in A. Igoni Barrett's Blackass Novel. The study felt under the realm of literary criticism, as the researcher analyzed and interpreted the literary work. Employing a sociological approach to the analysis, the study focused on the sociological aspects portrayed in the novel. Additionally, the analysis incorporated the interactional emphasis of identity theory as proposed by George McCall and J.L Simmons. Data for the research were drawn from A. Igoni Barrett's Blackass novel in the form of words, phrases, and utterances. The researcher gathered the data by identifying and categorizing relevant citations from the novel. Subsequently, the data were analyzed by describing and explaining the quotations based on the interactional emphasis of identity theory. The results of the analysis demonstrated that the prominent hierarchy significantly influences Furo's decision to alter his identity from his original